PEMILIHAN VENDOR JASA KEAMANAN DENGAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS - Fandi Ahmad (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
If an organization makes a wrong decision, it is certain that it can result in losses with a domino effect, especially in a depressed economic condition like today, for that decision selection must optimize the benefits of every possibility and minimize the losses that will be incurred. The purpose of this study is to assist in decision making and find out which vendor is best through a descriptive qualitative research approach with a focus on selecting security service vendors that will be used as a reference, the data in this study were obtained from the method of observation, interviews, and literature study to then be processed using the Analytical Hierarchy Process (AHP) approach by utilizing expert choice software in the hope of finding options that match the required criteria. From the research results it is known that there are four factors that are used as references in decision making, namely administrative, price, technical and qualification factors, with the alternative choice, namely PT. Handaru, PT. ABDI and PT. Wake up, after processing the data it is known that the best choice fell to PT. Handaru with a vector eigen value of 0.508 with an overall incostintency value of 0.02.